2021
DOI: 10.1093/nar/gkab191
|View full text |Cite
|
Sign up to set email alerts
|

INT-Hi-C reveals distinct chromatin architecture in endosperm and leaf tissues ofArabidopsis

Abstract: Higher-order chromatin structure undergoes striking changes in response to various developmental and environmental signals, causing distinct cell types to adopt specific chromatin organization. High throughput chromatin conformation capture (Hi-C) allows studying higher-order chromatin structure; however, this technique requires substantial amounts of starting material, which has limited the establishment of cell type-specific higher-order chromatin structure in plants. To overcome this limitation, we establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 86 publications
3
20
0
Order By: Relevance
“…Interestingly, after being packaged so compactly it manages in such a way that their distal regulatory elements remain accessible to their target gene for their regulation. Chromatin-chromatin interaction has been identified as an important mechanism for such regulation ( Li et al, 2012 ; Sun et al, 2020 ; Yadav et al, 2021 ). A distal element can specifically interact with its target gene situated on the same or different chromosome by looping ( Dean, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, after being packaged so compactly it manages in such a way that their distal regulatory elements remain accessible to their target gene for their regulation. Chromatin-chromatin interaction has been identified as an important mechanism for such regulation ( Li et al, 2012 ; Sun et al, 2020 ; Yadav et al, 2021 ). A distal element can specifically interact with its target gene situated on the same or different chromosome by looping ( Dean, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was shown that the timing of endosperm cellularization is epigenetically controlled [21]. Another study points out that the endosperm adopts a distinct high-order chromatin structure that differs from other cell types in other plant tissues [39]. It was speculated that genomic imprinting due to such unique arrangement in the endosperm chromatin structure allows the onset of gene activation of several important regulators prior to that of embryo [39].…”
Section: Underlying the Communications Route And Meansmentioning
confidence: 99%
“…Another study points out that the endosperm adopts a distinct high-order chromatin structure that differs from other cell types in other plant tissues [39]. It was speculated that genomic imprinting due to such unique arrangement in the endosperm chromatin structure allows the onset of gene activation of several important regulators prior to that of embryo [39]. However, understanding the detailed molecular mechanisms of the embryo-endosperm interaction requires more investigation.…”
Section: Underlying the Communications Route And Meansmentioning
confidence: 99%
“…The major obstacle has been technical difficulties in determining the chromatin state in plant cells. However, recent advanced techniques, such as high-throughput chromosome conformation method (Hi-C) and modification-specific intracellular antibodies (mintbodies), allow for the high-resolution detection of the chromatin structure and chromatin modifications in plants as well as in animals [ 108 , 115 , 116 ]. Further studies will identify the epigenetic factors involved in genome maintenance and local DNA repair/recombination processes through their interaction with repair machinery and cell-cycle regulators, thereby providing a new perspective on DDR mechanisms.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%